Considering aspects of history, knowledge and world-view Is Old Testament history relevant for South Africa? - Heyns, Dalene (Old Testament essays, 1997)
The relevance of Old Testament history for the present South Africa is considered within the larger framework of history in general and of different types of knowledge. Historical knowledge in the Old Testament, like all forms of knowledge and rationality, is embedded in its historical context and thus needs a 'creative hermeneutic' to interpret its meaning for today. The process entails the introduction of the present context(s) of the historian(s), creating the possibility of many different forms of interpretation and various explanations of meaning for diverse situations, thus relativising each explanation. In this way finding meaning in Old Testament history engenders humility and opens up possibilities for dialogue.